Effect of extraction procedure on the yield and biological activities of hydroxychavicol from Piper betle L. leaves - Zamakshshari, Norhisam; Ahmed, Idris A.; Nasharuddin, Muhammad N.A.; Mohd Hashim, Najihah; Mustafa, Mohammad R.; Othman, Rozana; Noordin, Mohamed I. (Elsevier GmbH., 2021)
Piper betle Linn is one of the most common ethnomedicinal plants with its extract being popularly used in the modern product to enhance functionality. However, extraction methods always lead to differences in biological activities. The objectives of this study were to evaluate the effects of the extraction methods on the yield and biological activities of hydroxychavicol from P. betle L. extracts and to determine the correlation between the hydroxychavicol content and biological activities of P. betle L. extracts such as antioxidant, antimicrobial, and anticancer properties. The purity of the hydroxychavicol and its concentration (quantitative) in the crude extracts were also evaluated using a reverse-phase HPLC while GC–MS was employed to determine other components (qualitative). The results showed that only certain extraction procedures gave high yields of hydroxychavicol as well as remarkable biological activities. The chloroform extract following boiling with water (M2) gave the highest percentage of hydroxychavicol content based on the HPLC analysis. M2 and pure hydroxychavicol actively inhibited all the five cancer cell lines studied except A549. M2 showed more effective inhibition activity against MCF 7 with an IC50 of 1.74 ug/mL. M2 extract also showed strong antibacterial activity against all the bacteria strains as well as a strong antifungal activity against Candida albicans. There was, however, a weak correlation between the hydroxychavicol content and the biological activities of P. betle L. extracts. In conclusion, extraction procedures greatly affect the yield and biological activities of hydroxychavicol from P. betle L. The designation of a single compound such as hydroxychavicol as a bioactive chemical marker compound in the P. betle L. extracts, however, is not enough to determine the biological activities of the extract.